Alectinib Induced SJS/TEN: A Case Report and a Review - ÇAĞLAR, Lidya Aden (Türk onkoloji dergisi, 2024)
Lung cancer is the second most common type of cancer in the world, adenocarcinoma is one of the most common variants with a rate of 35-40%.[1] Recent years, in NSCLC with relation to genetic alterations, biomolecular markers have emerged as a cornerstone of the advanced NSCLC treatment that overtook the standard chemotherapy.EGFR, ALK, ROS1, MET and BRAF are the most common driver mutations investigating in adenocarcinomas. Patients who had this rearrengements have been showed improved response rates and progression- free survival compared with chemotherapy.[2] The response rate range is 50 to 80% in targeted therapy. Overall survival was increased to between 18 and 38.6 months.[3,4]ALK mutation has seen approximately in %3-5 of the patients especially young age, nonsmoker female.[5] There are several types of ALK-TKI including first generation crizotinib; second generation alectinib, Ceritinib, Brigatinib and third generation, Lorlatinib.[6]Alectinib - an highly selective, oral second generation ALK-TKI has been currently preferred first-line therapy in ALK positive NSCLC based on ALEX, JALEX and ALESIA study.[7,8] Patients who had received Alectinib patients had significantly higher PFS rates (34.8 months vs. 10.9 months, HR: 0.43, 95% CI: 0.32-0.58) than Crizotinib.[9] Similarly, Peters et al.[10] demonstrated Crizotinib and alectinib PFS rates of 48.7% vs. 68.4%, respectively.At the updated ALEX study, median treatment duration of 28.1 months, among 152 patients, any-grade AEs were seen in 147 patients (97%), grade 3-5 AEs of 79 (52%). Furthermore, alectinib discontinuation, dose reduction and interruption were done due to AEs, 22 (15%), 31(20%), 40 (26%), respectively.[11] Rash was observed in 21 (13.8%) of patients in which grade-1 of 16 (10.5%); grade-2, 2 (1.3%), grade-3 2 (1.3%) and grade-4 1 (0.7%).[12]Herein we presented a patient with lung adenocarcinoma receieved Alectinib 1200 mg po for 90 days with a complete radiological response presented with skin rash which was consistent with SJS/TEN and controlled with high dose of steroid. With maintenance dose of steroid Alectinib desentitation was performed and after 2 weeks full dosage of alectinib could be achieved. In the literature, there were no reports that demonstrate the relation between toxicity and response. While the efficacy of targeted therapy has been well-established, the relationship between the severity of treatment-related toxicities and clinical response remains a subject of debate.Our case is noteworth because after desensitization with increasing dosage, response achieved maximally without any complication. We also highlight the response-toxicity relation by analyzing 6 cases in terms of approach, treatment and response in which alectinib-induced toxicity is occurred.Case: A 67 year-old never-smoking female, presented with dry cough and shortness of breath for 3 month symptoms increased progressively. PET/CT revealed primary lung cancer with bone, surrenal and pleural metastases, supraclavicular and mediastinal lymphadenopathies. Cranial MRI was compatible also with metastases. Supraclavicular lymph node biopsy confirmed lung adenocancarcinoma metastases. Alectinib 600 mg twice a day was commenced following the genetic test which revealed EM4-ALK fusion. After 45 days of treatment, maculopapular rashes started in abdominal region. The patient was followed up with a dermatologist for macular eruptions. Although antihistaminic therapy, itchy white skin that tends to coalesce widely on an erythematous base all over the body after 3 months of Alectinib. Punch biopsy taken from the right leg reported with no eosinophils and the findings were interpreted as a Drug Reaction because of MPO (Myeloperoxidase) positive - PMNLs (Polymorphonuclear neutrophils). Stevens-Johnson Syndrome was conceded and Alectinib was stopped with commencement of 1 mg/kg steroid threapy. There was no mucosal involvement in the patient whose skin involvement was 10-30% of the body surface area and was followed up with the diagnosis of SJS/TEN (Fig. 1). 5 days of iv steroids, antihistamines and topical lotions significant regression was detected in lesions.Fig. 1: Patient's initial presentation with maculopapular rashes in bilateral legs.After 3 months of Alectinib, PET/CT was consistent with metabolic complete radiological response. Furthermore, Cranial MRI demonstrated complete radiological response. Skin involvement was 10-30% and the patient followed up with the diagnosis of SJS/ TEN evaluated as Grade 4 cutaneous toxicity. The rash of the patient,who was followed up without Alectinib for 2 week, regressed and the prednisolone dose was reduced by 8 mg. Desentinization was started with a daily dose of 150 mg of alectiniB for 3 days than increased to 300 mg for 5 days, 600 mg for 7 days finally reached to therapeutic dose which is 1200 mg /day (Table 1). In the meantime the skin lesions resolved from grade 4 to grade 1 (Fig. 2). The patient continues to have a progression- free course with maintenance steroid therapy, and Alectinib is currently being administered at the full dose in the ninth month.Table 1: The desentization protocole we used in our caseFig. 2: Resolving eruptions following three months after the diagnosis of SJS/TEN.SJS/TEN: Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis.